Financial Constraints, Competition, and Hedging in Industry Equilibrium - ADAM, TIM; DASGUPTA, SUDIPTO; TITMAN, SHERIDAN (Journal of Finance, 2007)
ABSTRACT We analyze the hedging decisions of firms, within an equilibrium setting that allows us to examine how a firm's hedging choice depends on the hedging choices of its competitors. Within this equilibrium some firms hedge while others do not, even though all firms are ex ante identical. The fraction of firms that hedge depends on industry characteristics, such as the number of firms in the industry, the elasticity of demand, and the convexity of production costs. Consistent with prior empirical findings, the model predicts that there is more heterogeneity in the decision to hedge in the most competitive industries.